The effects of cultural intelligence on ASEAN mobility students’ sociocultural adjustment - Husin, Hartini; Ahmad, Fakhrorazi (2015)
Student mobility is one of the key strategic elements of cooperation which leads to development of a harmonized higher education environment among countries in Southeast Asia.The ASEAN International Mobility for Students (AIMS) program was initiated in 2009 purposely to encourage student mobility through multilateral collaborations among ASEAN member countries. In the context of globalization and challenging jobs market, the demand for highly qualified graduates who are able to cope in diverse cultural settings is in a serious need.As most universities view international students as a source of lucrative income and a critical success factor for international education marketing, it is imperative that the challenges that could reduce the learning effectiveness for international students should be minimised.As such, Cultural Intelligence (CQ), which is defined as a person’s capability to function effectively in situations characterised by culture diversity (Ang et al., 2007) may provide one of the solutions to minimise adjustment difficulties, specifically in integrating with the host country’s environment. Hence, this paper will introduce the concept of CQ and enlighten the role of CQ in promoting mobility students’ cross-cultural competence development. We propose a conceptual model, discussing the impacts of CQ on mobility students’ sociocultural adjustment. This paper also provides some insight on how CQ training could help mobility students in the ASEAN region to be well prepared to undertake study across the globe.